Changes of the slab structure of constitution scandate SrLaScO4 at the isovalent substitution of strontium atoms - Y.A.Titov; N.M. Belyavina; M.S.Slobodyanik; V.V.Chumak (Доповiдi Нацiональної академiї наук України, 2019)
The substitution conditions of scandium atoms in SrLaScO4 slab perovskite-like structure (SPS) of Sr1–xCaxLaScO4- type (0 ⩽ x ⩽ 0,3) have defined by X-ray powder diffraction methods. SPS (Abma space group) of Sr0.7Ca0.3LaScO4 phase with a substitution degree of strontium atoms equal 0,3 is determined by the Rietveld procedure. The crystal structure of Sr0.7Ca0.3LaScO4 is formed by two-dimensional perovskite-like blocks consisting of a slab of distorted ScO6 octahedra joined by vertices. Blocks are separated by the slab of (Sr, Ca, La)О9 polyhedra. Analysis of the obtained data has shown that, in a case of the substitution of Sr atoms by Ca atoms in SPS of Sr1–xCaxLaScO4, a gradual reduction of the length of the (Sr, Ca, La) — О2 interblock bond and the increases of the deformation degree (Δ) of interblock (Sr,Ca,La)О9 polyhedra and the mutual inclination of octahedrons ScO6 take place. Reduction in the distance between perovskite-like blocks approaches a construction of SPS to the thermodynamically stable perovskite structure, and the increase of Δ(Sr, Ca, La)О9 strains and destabilizes SPS. The total effect of these factors leads to the destruction of SPS, limits the range of Sr1–xCaxLaScO4 solid solutions with a slab perovskite-like structure (0 ⩽ x ⩽ 0,3), and makes the formation of SrLaScO4 scandate with this type of structure impossible. The results obtained can be used to regulate the functional (electrophysical, optical, etc.) structurally dependent properties of the Sr1–xCaxLaScO4 phases by successively isovalent substitution atoms in the A-positions of their layered perovskite-like structure.